KOMITMEN AFEKTIF DAN KOMITMEN NORMATIF DENGAN KINERJA PERAWAT DALAM PEMENUHAN ACTIVITY DAILY LIVING (ADL) - Nur Cholis; Kurniawati Kurniawati (STIKES Karya Husada Kediri, 2019)
The low of nurse performance in fulfillment of basic human needs of patients is a serious problem in health care. Organizational commitment is one of the factors influenced nurse performance, and this was inline with Meyer and Allen’s Theory. The aim of this study was to analyze the correlation of afective commitment and normative commitment toward nurse performance in fulfillment of basic human needs. This research was an analytical descriptive using correlation design with cross-sectional approach. The population of this study were all nurses who work in Wards of Madinah Islamic Hospital Kasembon and they taken by using purposive sampling method and obtained 27 respondents as the sample. The independent variable was affective and normative commitment and the dependent was nurse performance. Nurse performance was measured by using observing the respondents and the data collected by using observation form. Affective commitment and normative commitment were measured by using Organizational Commitment Questionnaire (OCQ). This data were analyzed by using Regression linier statistic test. The result of this study showed that there was correlation of affective commitment (t = 2,737 and α = 0,011), and normative commitment (t = 8,003 and α = 0,000) to nurse performance. The conclution of this study is the affective and normative commitments have significant positive effect toward nurse performance, with the most significant was normative commitment. Further research is expected to develop this research and be able to analyze more other factors are influence the nurse performance.